2012
DOI: 10.1002/adem.201100274
|View full text |Cite
|
Sign up to set email alerts
|

Improving Contour Accuracy and Strength of Reactive Air Brazed (RAB) Ceramic/Metal Joints by Controlling Interface Microstructure

Abstract: Nowadays with a rapid development of high temperature electrochemical devices, sealing technology is an issue of high practical relevance for the applicability of such equipment. Most commonly used joining technologies are glass joining, active metal brazing and reactive air brazing (RAB). [1] Glass joining is a relatively simple and cost-effective bonding method. However, for glass brazed joints, the maximum operation temperature is limited by the softening point of glass. [2,3] Active metal brazing requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…[13]. After the brazing process, typically numerous large pores were found within the cell joint due to the limited wetting ability of silver based brazes on ceramic surfaces, which is discussed in detail in ref.…”
Section: Stack Manufacturing and Start-upmentioning
confidence: 99%
“…[13]. After the brazing process, typically numerous large pores were found within the cell joint due to the limited wetting ability of silver based brazes on ceramic surfaces, which is discussed in detail in ref.…”
Section: Stack Manufacturing and Start-upmentioning
confidence: 99%
“…However, only few mechanical characterization results of metal-based SOFC sealants are available from literature, which furthermore concentrate on the evaluation of braze compositions, [2][3][4] the impact of the chemical composition of the joint interfacial reaction layers on fracture energy and crack path location [5,6] as well as time-dependent changes of the aforementioned issues during isothermal stack operation. [7,8] Mechanical behavior of the metallic braze matrix and possible implications for the loading situation at the interfaces are still widely disregarded topics, because reliable high temperature testing techniques utilizing miniature specimens have to be developed and successfully applied for characterization.…”
Section: Introductionmentioning
confidence: 99%
“…As Ag melts in air on an inert substrate at around 945°C it can be concluded that elements of the steel diffuse into the Ag shifting the solidus temperature. [19] This indicates that the added Al does not influence the melting reaction. The fact that no exothermic peak occurs explains why no distinct reaction zone can be observed in the cross-sections except the oxide layer of the steel itself.…”
Section: Thermochemical Behaviormentioning
confidence: 83%
“…[13][14][15][16] As the standard Cu-containing filler metals lead to the formation of a thick reaction layer on the steel endangering the strength of the joint, alternative Cu-free filler metals were investigated to avoid the growth of the reaction layer. [17][18][19][20] In the gas separation modules or the SOFCs where the RAB was used only base materials with matching CTE values were used as base material (BSCF/AISI 314 and 3YSZ/Crofer 22 H). This limits the materials that can be joined by RAB and consequently the range of application.…”
Section: Introductionmentioning
confidence: 99%